2012
DOI: 10.1155/2012/319785
|View full text |Cite
|
Sign up to set email alerts
|

Distortion-Based Slice Level Prioritization for Real-Time Video over QoS-Enabled Wireless Networks

Abstract: This paper presents a prioritization scheme based on an analysis of the impact on objective video quality when dropping individual slices from coded video streams. It is shown that giving higher-priority classified packets preference in accessing the wireless media results in considerable quality gain (up to 3 dB in tests) over the case when no prioritization is applied. The proposed scheme is demonstrated for an IEEE 802.11e quality-of-service-(QoS-) enabled wireless LAN. Though more complex prioritization sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The work ensures that the real-time was guaranteed while allowing a limited loss of frames. Ali et al [11] proposed distortion-based slice level prioritization for real-time video over QoS-enabled wireless networks. The work showed that given a higher-priority to some classified packets in accessing the wireless media, a considerable quality was achieved when prioritization is not used.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The work ensures that the real-time was guaranteed while allowing a limited loss of frames. Ali et al [11] proposed distortion-based slice level prioritization for real-time video over QoS-enabled wireless networks. The work showed that given a higher-priority to some classified packets in accessing the wireless media, a considerable quality was achieved when prioritization is not used.…”
Section: Related Workmentioning
confidence: 99%
“…In designing a proficient MAC protocol for wireless networks, the characteristics like energy efficiency, scalability, adaptively, latency, channel utilization, throughput and fairness must be considered [10,11] . Collision occurs in wireless networks once two nodes transfer data at a time over transmission medium.…”
Section: Introductionmentioning
confidence: 99%